2023
DOI: 10.36877/pmmb.a0000273
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the impact of Helicobacter pylori and potential gut microbiome modulation

Abstract: Helicobacter pylori is a highly prevalent bacteria that can harm humans due to its major involvement in developing gastrointestinal diseases, particularly gastric cancer. Therefore, eradicating H. pylori is one of the most important strategies for preventing gastric cancer. Antibiotic treatment has always been the gold standard treatment for H. pylori infection. However, the decreasing efficacy of antibiotic therapy due to the rising antibiotic resistance and high incidence of dysbiosis-related adverse effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 153 publications
0
3
0
Order By: Relevance
“…Gastrointestinal infections, such as Helicobacter pylori infection and foodborne illnesses, have also been linked to dysbiosis [27][28][29]. H. pylori is a bacterium that colonizes the stomach and is associated with various gastrointestinal disorders, including gastric ulcers and stomach cancer.…”
Section: Microbiome Dysbiosis and Infectious Diseasesmentioning
confidence: 99%
“…Gastrointestinal infections, such as Helicobacter pylori infection and foodborne illnesses, have also been linked to dysbiosis [27][28][29]. H. pylori is a bacterium that colonizes the stomach and is associated with various gastrointestinal disorders, including gastric ulcers and stomach cancer.…”
Section: Microbiome Dysbiosis and Infectious Diseasesmentioning
confidence: 99%
“…However, the sustainability of the baseline microbial pattern becomes a matter of concern owing to the possibly harmful interference of various internal and external stimuli at any given stage of life [ 64 , 68 , 69 ]. An untoward perturbation of the baseline gut microbial composition favors the pathogenic activity of the indigenous symbionts of the gut, hence giving rise to pathobionts that may, in turn, adversely affect the host’s physiology [ 70 , 71 , 72 , 73 , 74 , 75 ].…”
Section: Rudiments Of Probiotics: Human Gut Microbiota and Gut Dysbiosismentioning
confidence: 99%
“…Furthermore, the pathogen dynamics with the microbiota of the gastrointestinal tract is highly complex, and eradication not only affects the gastrointestinal tract itself, but also its absence has been associated with dysbiosis and the emergence of a variety of systemic disorders, weight gain or loss, and susceptibility to allergic diseases such as asthma [43,[74][75][76][77][78][79]. In contrast, research over the years has demonstrated that eradicating H. pylori prior to the onset of precancerous histological changes can prevent the development of gastric cancer and dysbiosis can be managed with the integration to the antibiotic treatment of probiotics and other alternatives for microbiota modulation [80][81][82]. This forms the basis for the screen-and-treat approach to H. pylori infection and optimization strategies such as family-based.…”
Section: Introductionmentioning
confidence: 99%